Rules of anatomy in Islamic law - Muhammad Husni, Ahmad; Muhammad Husni, Amin (Zes Rokman Resources, 2020)
This article talks about anatomy in Islamic law. Anatomy has become widespread in many hospitals for various purposes. It is very necessary in our time, especially the educative anatomy that teaches doctors parts of human body to help them in treating people. Criminal anatomy is also important to know how someone has been killed; it is very important as through it innocence and guilt could be established. Pathology is very essential as well, to know the types of sickness that affect human which can be avoided by knowing it. The problem is that we must know the rule of shariah regarding anatomy and its classifications, and to know the rule of buying corpse for the purposes of anatomy. I have adopted inductive and analytical approach to highlight the view of the jurists on that issue and the conditions that must be observed on the anatomy of corpse. The most important results we reached are: Among the most important principles by Islam is the inviolability of human, his blood and body, and they cannot be exposed except by a reason of the shariah, and that human must be respected and that tempering with his body with something unbeneficial must be avoided.